Intervention of Virtual Reality on Mental Health - KNVS Mansvi; J. P. Pramod (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Virtual Reality (VR) is quickly becoming a game-changing technology for treating mental health issues. Virtual reality (VR) enables people to safely and engagingly confront and manage their psychological difficulties by creating immersive and regulated environments. This study investigates how virtual reality can be used to treat illnesses like depression, phobias, anxiety disorders, and post-traumatic stress disorder (PTSD). It provides a special fusion of customization and real-time feedback, it demonstrates the promise of virtual reality for exposure treatment, relaxation training, and cognitive rehabilitation. The technology is positioned as a promising addition to conventional therapy techniques because of its capacity to mimic real-world situations and offer customized therapeutic experiences. Notwithstanding its advantages, issues including cost, accessibility, and the requirement for further empirical support still exist. Utilizing virtual reality in mental health care develops more efficient, scalable, and inclusive therapeutic solutions, this study highlights the significance of interdisciplinary collaboration.